2006
DOI: 10.1002/ajmg.b.30450
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S‐transferase polymorphisms and onset age in α‐synuclein A53T mutant Parkinson's disease

Abstract: Monogenic forms of Parkinson's disease (PD) provide an opportunity to examine mechanisms underlying phenotypic variation. Glutathione S-transferase (GST) has detoxification and antioxidative functions. To screen genetic variations in GST for an effect on the onset age (OA) of PD, we typed seven common genetic polymorphisms in five GST isoenzymes, M1, M3, P1, T1, and Z1, in 36 affected individuals of Italian or Greek origin with the alpha-synuclein A53T (PARK1) mutation. Mean OA was 45.2 years with a wide SD of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Of the six classes of GST (alpha, zeta, mu, pi, omega and theta), only GST pi has been shown to express in substantia nigrial neurons (31) and GSTP1 is a part of the GST pi sub-family. It has been reported that neuronal cells harboring mutated and inactivated GSTP1 was more susceptible to 1-methyl-1,4 phenyl 1,2,3,6 tetrahydropyridine (MPTP) (3637). Moreover, members of the GSTP1 has also been reported to inhibit JNK signaling pathway via blocking c-Jun phosphorylation and hence apoptosis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Of the six classes of GST (alpha, zeta, mu, pi, omega and theta), only GST pi has been shown to express in substantia nigrial neurons (31) and GSTP1 is a part of the GST pi sub-family. It has been reported that neuronal cells harboring mutated and inactivated GSTP1 was more susceptible to 1-methyl-1,4 phenyl 1,2,3,6 tetrahydropyridine (MPTP) (3637). Moreover, members of the GSTP1 has also been reported to inhibit JNK signaling pathway via blocking c-Jun phosphorylation and hence apoptosis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Data from our laboratory have shown that GSTP1 wildtype allele is an individual protective genetic trait in idiopathic PD (Golbe et al 2007;Vilar et al 2007) and GSTpi polymorphism has been shown to enhance dopaminergic neuron loss in a parkin transgenic Drosophila model (Whitworth et al 2005) protein expression in both the MPTP-sensitive C57BL/6 and the MPTP-resistant Swiss-Webster mouse strains immediately after the insult. This depletion was followed by a recovery to basal levels of GSTpi, indicative of de novo synthesis of the enzyme in response to xenobiotic exposure (Smeyne et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these evidences suggest that the level of GSTpi expression is crucial in determining cell sensitivity to a broad spectrum of toxic chemicals (Hayes and Pulford 1995), therefore ameliorating the oxidative milieu especially prevalent in dopaminergic neurons. Recent epidemiological studies from our own group (Vilar et al 2007) and others (Golbe et al 2007) indicate that GSTP wild-type allele is an individual protective genetic trait in idiopathic PD. In fact, there is good evidence that the GSTP polymorphisms affect substrate selectivity and stability increasing the susceptibility to parkinsonism-inducing effects of environmental toxins (Hayes and Strange 2000).…”
Section: Introductionmentioning
confidence: 95%
“…For example, Golbe et al reported that age of onset in individuals carrying the A53T alpha-synuclein (PARK1) mutation is positively associated with a GSTpi G-for-A nucleotide substitution at position 313 [159], while McCormick et al identified polymorphisms in GSTpi that correlate with increased risk of PD after exposure to pesticides [160]. Additionally, DePalma et al reported a marked increase in association of PD with a GSTT1*0 polymorphism when correlated with other PD risk factors, such as rural living and well water consumption [158].…”
Section: Reduction Of Free Radicals By Glutathione Conjugating Enzymesmentioning
confidence: 99%